Banjarmasin City Government Efforts in Giving Access to Public Services and Regional Equipment Organizational Accountability - Mercy Pasande; Wirman Syafri (International Journal of Regional Innovation, 2023)
This research combines public service access and the accountability of Regional Device Organizations into a single application within the Banjarmasin City Government. The innovations of Banjarmasin Pintar and the Personnel Performance Information System (SIKAP) are utilized to enhance the effectiveness of public services and the accountability of government agencies. Banjarmasin Pintar is an application that integrates various public services using Single Sign-On (SSO) technology, allowing users to access all services with a single account. ATTITUDE is a performance accountability system that covers planning, reporting, and financial realization. The research methodology employed is a qualitative approach with data collection through literature review.